Fenomena Mandi Lumpur Live di Tiktok Menurut Teori Dramaturgi Erving Goffman - Jannah, Wardatul; Fasadena, Nova Saha (Jisab, 2023)
Tiktok is a medium to be able to interact with viewers. With that interaction, the number of content creators has increased with various kinds of ideas, one of which is the mud bath which has become a phenomenon. For this reason, researchers are interested in researching using media analysis using Erving Goffman's theory of dramaturgy. The results of the research are that the object that is used as the frontstage is the grandmother who was poured with mud water with the aim of getting gifts from viewers. Meanwhile, those who become the backstage are account owners who use the media to act as directors as well as communicate with viewers and use various strategies so that they get more gifts.